Trends in Topical Prescriptional Therapy for Old Patients With Dry Eye Disease in Six Major Areas of China: 2013–2019 - Yu, Zhenwei; Wu, Xiaoyan; Zhu, Jianping; Jin, Jiayi; Zhao, Yuhua; Yu, Lingyan (Frontiers in Pharmacology, 2021)
The prevalence of dry eye disease (DED) in old patients are high, corresponding to a substantial economic burden. In this cross-sectional study, we analyzed the trends in the topical prescriptional treatment of old patients with DED in six major areas of China. Information on topical drug prescriptions for DED patients aged above 60 years was extracted from the Hospital Prescription Analysis Cooperative Program of China database. Trends in yearly prescriptions and cost were analyzed. The data were further stratified by patient age and sex, drug class, and specific drug. A total of 130,734 prescriptions from 52 hospitals located in six major areas of China were analyzed. The number of prescripptions per year for patients with DED increased from 13,308 in 2013 to 22,074 in 2019, with a corresponding increase in cost of all topical drugs from 1,490,014 Chinese Yuan (CNY) to 2,618,206 CNY. Drugs for the treatment of DED accounted for the largest proportion of the total cost in each year. Ocular lubricants were the main pharmacotherapy agent. Sodium hyaluronate use increased over time, and the drug was used by 65.9% of patients by the end of the study. Pranoprofen was the second most frequently used drug. The most frequently used drugs for co-incident disease were antimicrobials. Treatment patterns for DED haven’t changed, and the most frequently used drug combination was sodium hyaluronate and pranoprofen. In summary, prescription for old patients with DED and the cost of treatment are increasing. Ocular lubricants are the main treatment option, while sodium hyaluronate is the most frequently used drug. The observed trends can lead to more efficient allocation of health care resources in China.